INVESTIGATION OF PREVALENCE OF RUBELLA AMONG WOMEN OF PREMARITAL AND PRECONCEPTIONAL AGE - D.D Farhud; H. Sadighi; A.A. Solati; Z. Alinejad; Sh. Mohammad-Ebrahim (Tehran University of Medical Sciences, 1995)
An evaluation of the prevalence of immune status to rubella was made among 1151 premarital and preconceptional counseled females (17-40 years old) visiting the Genetic Clinic in Tehran. Population of Tehran, like any other large city, consists of mixtures of various communities and ethnic groups in the country. The method of analysis was rubella haemagglutination inhibition (Hl.) test. Immunity to rubella was observed in 97.14% of the population and most was immune before the age of 29. This high prevalence of positive cases shows a change in the community orientation by more social participation and mixing such as attendance of kindergarten. Because of the high prevalence obtained for rubella immunity, instead of general vaccination programs, measurement of rubella titer is recommended for each premarital or preconceptional female individual.